Qualitative Analysis Of Bottled Drinking Water And Refilled Drinking Water Sold Around University Of Muhammadiyah - Rusidah, Yunita; Farikhah, Lailatul; Mundriyastutik, Yayuk (Prosiding University Research Colloquium, 2021)
This study aims to determine the quality of bottled drinking water and refilled drinking water that sold around University of Muhammadiyah Kudus.It is in terms of physical, chemical, and microbiological parameters of drinking water based on SNI 01- 3554-2006 and PMK no. 492 of 2010. The test was conducted byten samples of mineral water. Those are seven bottled drinking water (Ades, Airmu, Aqua, Cleo, Crystalin, Le mineral and Vit) and three samples of AMIU was taken from refill drinking water depots around campus, from depots in Pasuruhan, Prambatan, and Purwosari. The research was conducted at PT Sariguna Primatirta Kudus. It is a factory inKudus city which has testing requirements. The tests carried out chemical physics which included testing of TDS, pH, and three heavy metal elements and included testing of content of Fe, Mn and Cl2 (chlorine) elements, and microbiology namely TPC of presence of E-coli and Total Coliform. The results of physical and chemical measurements through total dissolved solid (TDS) showed that Airmu and Cleo under 10 ppm (demineral) and below 500 ppm for 8 samples of mineral water.It is according to the TDS requirements of SNI, > 10 ppm for demineralized and> 500 ppm for mineral water. The results of the pH test or the degree of acidity are in normal pH which are around 7 of 9 samples and only one with an alkaline condition is 8.37, namely sample from the Pasuruhan depot. The test for the presence of heavy metals, Fe, Mn,is in good condition, showing the number zero with the brand test kit. In addition, for testing the presence of chlorine content, the results were above the threshold, namely 0.05 ppm from the Pasuruhan depot water sample, 0.02 ppm from the Prambat depot and the Purwosari depot. This is not in accordance with SNI provisions for chlorine content of 0 ppm. Meanwhile, microbiologically of the TPC showed before dilution were only Cleo and Ades which were suitable for consumption because they were absent from bacterial contamination. While the TPC results after dilution, testing the difference between E-Coli and Total coliform resulted in 7 samples of bottled drinking water which were safe and feasible as drinking water according to SNI 01-3553-2006 and 3 samples AMIU were not fulfilled to PMK No. 492/2010 as drinking water requirements.